Forms of embodiment in lived religion = Formy ucieleśnienia w religii przeżywanej - Sztajer, Sławomir (Przegla̜d religioznawczy, 2021)
The article discusses various forms of embodiment in lived religion and different ways of studying them. It focuses on three approaches to embodiment: the study of religious subjectivity that involves experiencing one’s own body, the study of shared cultural representations of the body, and the study of determinants that change body states and thus influence religious thought and behavior. It is argued that embodiment in lived religion does not just mean that the body is at the center of religious life. Embodiment manifest itself in all dimensions of religious life from ritual behavior to ineffable religious experience. It is most clearly seen in everyday religious activity that forms the core of lived religion.